Mortality and cardiac resynchronization therapy with or without defibrillation in primary prevention. Issue 8 (28th June 2020) - Gras, Matthieu; Bisson, Arnaud; Bodin, Alexandre; Herbert, Julien; Babuty, Dominique; Pierre, Bertrand; Clementy, Nicolas; Fauchier, Laurent
Abstract: Aims : Cardiac resynchronization therapy with (CRTD) or without (CRTP) defibrillator is recommended in selected patient with systolic chronic heart failure and wide QRS. There is no guideline firmly indicating choice between CRTP and CRTD in primary prevention, particularly in older patients. Methods and results : Based on the French administrative hospital-discharge database, information was collected from 2010 to 2017 for all patients implanted with CRTP or CRTD in primary prevention. Outcome analyses were undertaken in the total study population and in propensity-matched samples. During follow-up (913 days, SD 841, median 701, IQR 151–1493), 45 697 patients were analysed (CRTP 19 266 and CRTD 26 431). Incidence rate (%patient/year) of all-cause mortality was higher in CRTP patients (11.6%) than in CRTD patients (6.8%) [hazard ratio (HR) 1.70, 95% confidence interval (CI) 1.63–1.76, P < 0.001]. After propensity-matched analyses, mortality of patients over 75 years old with non-ischaemic cardiomyopathy (NICM) was not different with CRTP and CRTD (HR 0.93, 95% CI 0.80–1.09, P = 0.39). The CRTP patients under 75 years old with NICM had a higher mortality than CRTD patients (HR 1.22, 95% CI 1.03–1.45, P = 0.02). Mortality rate was also higher with CRTP than with CRTD irrespectively of age in patients with ischaemic cardiomyopathy (ICM) (<75 years old: HR 1.22, 95% CI 1.08–1.37, P = 0.01; ≥75 years old: HR 1.13, 95% CI 1.04–1.22, P = 0.003). Conclusion : In this real-life study, CRTD was associated with a significantly lower all-cause mortality than CRTP in patients with ICM and in patients with NICM under 75 years old. Patients over 75 years old with NICM did not have lower mortality with primary prevention CRTD implantation.